2020
DOI: 10.3390/ijms21113877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proton Pump Inhibitors on Colorectal Cancer

Abstract: Proton pump inhibitors (PPIs) are administered commonly to aged people; however, their effect on colorectal cancer (CRC) has still not been fully elucidated. Here, we examined the effect of PPIs and consequent alkalization on CRC cells. PPI administration alkalized the fecal pH and increased serum gastrin concentration. PPI and pH8 treatment (alkalization) of CMT93 mouse colon cancer cells inhibited cell growth and invasion, increased oxidative stress and apoptosis, and decreased mitochondrial volume and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…[43][44][45][46][47] In addition, long-term use of PPIs was suggested to significantly alter the abundance and microbial diversity of gastrointestinal symbiotic bacteria and to promote activation of related proteins or production of carcinogenic substances, which was also associated with the development of related cancers. 16,48,49 Specifically, in pancreatic cancer, prolonged acid-suppression may promote nitrate-reducing bacteria to produce potential carcinogenic N-nitroso compounds, which would cause further pancreatic damage and even pancreatic cancer. 50 As for colorectal cancer, it was demonstrated that PPIs administration would promote growth of Clostridium perfringens and induce significant release of their enterotoxin to stimulate the progression of colorectal cancer by activating yes-associated protein.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46][47] In addition, long-term use of PPIs was suggested to significantly alter the abundance and microbial diversity of gastrointestinal symbiotic bacteria and to promote activation of related proteins or production of carcinogenic substances, which was also associated with the development of related cancers. 16,48,49 Specifically, in pancreatic cancer, prolonged acid-suppression may promote nitrate-reducing bacteria to produce potential carcinogenic N-nitroso compounds, which would cause further pancreatic damage and even pancreatic cancer. 50 As for colorectal cancer, it was demonstrated that PPIs administration would promote growth of Clostridium perfringens and induce significant release of their enterotoxin to stimulate the progression of colorectal cancer by activating yes-associated protein.…”
Section: Discussionmentioning
confidence: 99%
“…This complex is known as a “multi-protein membrane pore complex” and causes the lysis of cancerous cells through losing cellular osmotic equilibrium. The anti-cancer feature of CEP for CRC cells was confirmed in in vivo and in vitro studies [ 46 , 47 ]. For instance, Pahle et al , (2017) verified an optimized CPE expressing vector as a target for claudin-3 and/or claudin-4 expressing in colon cancer cells including SW-480, HCT-116, SW620, Caco-2, HT-29 and PDX (patient-derived colon carcinoma xenografts).…”
Section: Introductionmentioning
confidence: 93%
“…Notably, patients on PPIs showed decreased levels of cyclin D1 (35). Additional studies found that the expression of cyclin D1 is significantly reduced in pancreatic and colorectal cancer cells treated with PPIs (36). Given their FDA-approval, the pleiotropic effect of PPIs to maintain the expression of Bax and to decrease cyclin D1 levels may be an attractive strategy to overcome the resistance of cancer cells to radiation therapy.…”
Section: Adaptive Pathwaymentioning
confidence: 99%